2015
DOI: 10.1016/j.jocd.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Precision Error in Dual-Energy X-Ray Absorptiometry Body Composition Measurements in Elite Male Rugby League Players

Abstract: Body composition analysis using dual-energy X-ray absorptiometry (DXA) is becoming increasingly popular in both clinical and sports science settings. Obesity, characterized by high fat mass (FM), is associated with larger precision errors; however, precision error for athletic groups with high levels of lean mass (LM) are unclear. Total (TB) and regional (limbs and trunk) body composition were determined from 2 consecutive total body scans (GE Lunar iDXA) with re-positioning in 45 elite male rugby league playe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
10
23
0
Order By: Relevance
“…For this reason, anthropometry regression equations were not used to assess change, instead utilising the S7SF as a comparison measure. This study found strong linear associations between the methodologies when assessing change in FM, with the S7SF able to predict the direction of change 83% of the time, or 91% when DXA FM change >1kg, which is approximately the threshold for least significant change previously reported in a similar population (Barlow et al, 2015). Despite this, the relative changes estimated by S7SF will be 4.6-7.0% different in magnitude from those measured by DXA, potentially due to questions raised about the reliability of DXA for assessing FM, particularly in lean individuals (Prior et al, 2001;Toombs et al, 2012;Van Der Pleog et al, 2003;Williams et al, 2006).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For this reason, anthropometry regression equations were not used to assess change, instead utilising the S7SF as a comparison measure. This study found strong linear associations between the methodologies when assessing change in FM, with the S7SF able to predict the direction of change 83% of the time, or 91% when DXA FM change >1kg, which is approximately the threshold for least significant change previously reported in a similar population (Barlow et al, 2015). Despite this, the relative changes estimated by S7SF will be 4.6-7.0% different in magnitude from those measured by DXA, potentially due to questions raised about the reliability of DXA for assessing FM, particularly in lean individuals (Prior et al, 2001;Toombs et al, 2012;Van Der Pleog et al, 2003;Williams et al, 2006).…”
Section: Discussionsupporting
confidence: 63%
“…The findings suggest that the LMI may not be able to detect small changes in FFM (<1.6% or ~1.5 kg in this population), and may be slightly less reliable for backs. However, in the majority of cases (83%) the LMI was able to indicate the change in direction of DXA FFM when changes were >1 kg, which is approximately the threshold for least significant change for DXA previously proposed in rugby union athletes (Barlow et al, 2015).…”
Section: Discussionmentioning
confidence: 66%
“…The precision error findings for total body lean and fat mass derived using both hand positioning protocols are within ISCD recommended ranges (12) and are similar to those reported by other studies in men athletes (LM 0.21 kg, 0.3%; FM 0.17 kg, 1.5 %) (18), senior rugby league players (LM 0.36 kg, 2.4%; FM 0.33 kg, 2.9 %) (19) and normal (LM 0.22 kg, 0.5%; FM 0.18 kg, 1.0%, LM 0.24 kg, 0.5%; FM 0.20 kg, 0.8%) (20,21). Precision error should be reported for both RMS SD and %CV though, highlighted by Carver and co-workers whose study in obese subjects reported similar %CV values (LM 1.0% and FM 0.9%), with reported RMS SD values at a factor of three higher than the studies cited above (22).…”
Section: Discussionsupporting
confidence: 88%
“…populations [1,3], DXA is now widely accepted as a practical criterion method for assessing fat mass in athletes [33]. However, there are logistical and financial costs associated with DXA measurements that might prevent its frequent use in sports settings.…”
Section: Introductionmentioning
confidence: 99%